The effect of twin-shock on monetary and fiscal policies in Indonesia - Utama, Chandra (Penerbit Universiti Kebangsaan Malaysia, 2020)
The research aims to investigate whether the monetary and fiscal policies in Indonesia interact with each other as well as the effect of twin shock on the coordination. The study employs the cointegration analysis and Error Correction Model (ECM) to estimate quarterly data from 2001:1 to 2016:4. The study has found the existence of consolidated government budget constraint (GBC) that links the activities of fiscal authority (taxing, spending, and issuing the bond) with the activities of the monetary authority in the short and long run. The study also found the coordination between monetary and fiscal policies both in the short and long run. It is found that the short-run fiscal policy was influenced by the long-run shock of the exchange rate and the short-run monetary policy was influenced by the short and long-run shock of the price level. The study shows the importance of policy coordination in the currency and budget deficit management.